Pengaruh Lokasi dan Fasilitas terhadap Keputusan Pembelian Rumah pada Perumahan Green Rahayu Tahap 2 Setu Kabupaten Bekasi: The Influence of Location and Facilities on the Decision to Buy a House in Green Rahayu Housing Phase 2 Setu, Bekasi Regency - Melly Melly; Irwin Sukrisno Soegeng; Andri Rizko Yulianto (Jurnal Mnajemen | Ekonomi | Akuntansi, 2026)
This study aims to analyze the effect of location (X1) and facilities (X2) on the house purchase decision (Y) at Perumahan Green Rahayu Tahap 2 developed by PT Indo Megah Abadi in Setu District, Bekasi Regency, both partially and simultaneously. A quantitative method with a saturated sampling technique was applied to 100 consumers who had purchased a house in the housing complex. Data were collected via Likert-scale questionnaires and analyzed using multiple linear regression with SPSS 27. The t-test results show that location has a significant partial effect (t=6.785; Sig.=0.000), as does facilities (t=4.018; Sig.=0.000). The F-test indicates a significant simultaneous effect (F=34.284; Sig.=0.000). An R Square of 0.414 indicates both variables explain 41.4% of the variation in purchase decision. Location contributes more dominantly (28.09%) than facilities (9.86%). These findings enrich property marketing research in peri-urban areas that have not been widely studied.